2013
DOI: 10.2214/ajr.11.8394
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and Interpretation Time of Computer-Aided Detection Among Novice and Experienced Breast MRI Readers

Abstract: OBJECTIVE The purpose of this study was to compare the diagnostic accuracy and interpretation times of breast MRI with and without use of a computer-aided detection (CAD) system by novice and experienced readers. SUBJECTS AND METHODS A reader study was undertaken with 20 radiologists, nine experienced and 11 novice. Each radiologist participated in two reading sessions spaced 6 months apart that consisted of 70 cases (27 benign, 43 malignant), read with and without CAD assistance. Sensitivity, specificity, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 29 publications
1
24
0
Order By: Relevance
“…This work demonstrates the ability of DTI, scanned at 3 T at high spatial resolution (~8 mm 3 ), to measure in vivo the water diffusion tensor parameters in the entire fibroglandular tissue of both breasts. The ensemble of algorithms and software developed in the course of this study enabled analysis of the large DTI datasets and simultaneously view the diffusion parametric maps of the various diffusion coefficients, λ 1 , λ 2 , λ 3 , ADC and anisotropy indices λ 1 -λ 3 , and FA of all breast slices.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…This work demonstrates the ability of DTI, scanned at 3 T at high spatial resolution (~8 mm 3 ), to measure in vivo the water diffusion tensor parameters in the entire fibroglandular tissue of both breasts. The ensemble of algorithms and software developed in the course of this study enabled analysis of the large DTI datasets and simultaneously view the diffusion parametric maps of the various diffusion coefficients, λ 1 , λ 2 , λ 3 , ADC and anisotropy indices λ 1 -λ 3 , and FA of all breast slices.…”
Section: Discussionmentioning
confidence: 79%
“…The insufficient sensitivity and specificity of these techniques, particularly for detecting lesions in dense breasts, has stimulated the development of other techniques including breast magnetic resonance imaging (MRI). Dynamic contrast enhanced (DCE) MRI has been established as a powerful tool for the detection and diagnosis of breast cancer 1,2 and is frequently facilitated by computer aided diagnosis means 3 . Currently it is used for special cases, such as high risk patients 4 , but not for routine screening, presumably because of the high costs, the need to use an injection of a contrast agent, the lack of standardization and the variable specificity in differentiating benign from malignant lesions ranging from low/moderate values 5,6 to high values that were obtained using combined mammography and DCE-MRI 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…Systematic review and meta-analysis have demonstrated that clinical CAD systems do not influence the sensitivity or specificity of an experienced radiologist. 27,28 However, our results suggest that features extracted by the computer, imperceptible to the radiologists eye, may further our understanding of breast cancer molecular subtypes. Technology has allowed MRI to move beyond diagnosis, as shown by ours and other reports of extraction of histogram based features and use of fractal-based methods and/or multiparametric analysis that may offer further insight into a complex heterogeneous disease on a pixel-by-pixel level.…”
Section: Discussionmentioning
confidence: 90%
“…Patients underwent T1-weighted precontrast and three to six postcontrast sequences with a gadolinium-based contrast agent. Because algorithms have not provided consistent benefits for experienced radiologists (31,32).…”
Section: Imaging Datamentioning
confidence: 99%